Ecosystem Service and Land-Use Changes in Asia: Implications for Regional Sustainability (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book highlights the role of research in Ecosystem Services and Land Use Changes in Asia. The contributions include case studies that explore the impacts of direct and indirect drivers affecting provision of ecosystem services in Asian countries, including China, India, Mongolia, Sri Lanka, and Vietnam. Findings from these empirical studies contribute to developing sustainability in Asia at both local and regional scales.